Template Synthesis and Spectroscopic Characterization of Some Schiff Base Complexes of Transition Metal Ions - Maihub, A.A.; El-Ajaily, M.M.; Ben-Saber, S.M.; Naghmush, A. (Asian Journal of Chemistry, 2010)
Schiff bases having biological activities are used as ligands have been synthesized and analyzed. The synthesis of a Schiff base by condensing benzoin with 4-aminophenazone in an ethanolic medium on the addition of divalent and trivalent transition metal ions was investigated. All the metal Schiff base chelates of the formulae [ML(OH)X(H2O )w].nH2O, in which M represents the divalent transition metal ions of Mn, Ni and Cu and trivalent transition metal ions of Cr and Fe; x = 1 or 2, w = 0, 1 or 2 and n = 0, 5, 6 or 7 have been isolated. These chelates were characterized by elemental analysis, molar conductance measurements, infrared and electronic absorption spectra.